Improvement and Optimization of the Structure of the Driving Drum based on ANSYS - Yu Yuzhen; Wang Fei; Dong Xiaolei; Li Li; Liu Liwei (Jixie chuandong)
The finite element analysis software ANSYS is applied to conduct the finite element analysis of the driving drum,and the stress and deformation conditions are obtained. According to the result,the structure redesign and lightweight research of the driving drum are carried out,and the lightweight results are verified.Finally,the multi-objective optimization design of the driving drum is carried out by using optimization module of ANSYS Workbench,which provides a theoretical basis for the optimization and improvement of the driving drum structure.